THE IMPORTANCE OF INTEGRATIVE MOTIVATION IN SECOND LANGUAGE (Conference Zone, 2022)
Students that are motivated are more likely to exert greater effort in their academic endeavors by persevering through the learning process. The goal of the study was to determine and examine whether instrumental or integrative motivation promotes. Vocabulary and grammar are the most common areas of difficulty for students learning English as a second language, according to this research, which also shows how these issues affect their speaking and writing.